Do University Presidents Make a Difference? A Strategic Leadership Theory of University Retrenchment - Budros, Art (Canadian Journal of Higher Education, 2002)
Although the general consensus is that university presidents do not make a difference, most research on this issue is atheoretical and perceptual in nature. Consequently, I draw on strategic leadership theory to examine whether observable experiences of presidents affected the adoption of retrenchment (early faculty retirement) plans among Ontario universities from 1989-90 to 1997-98. In doing so, I also advance strategic leadership theory by introducing novel measures of leaders’ observable experiences and by testing their impact on an outcome (retrenchment) in a noncorporate setting. Since early faculty retirement plans have spread across universities, and since evidence indicates that they combine financial benefits and academic costs, their adoption represents a key structural change begging for explanation. Although the literature attributes the adoptions to uncontrollable forces, I report that presidents play a major role in the adoptions. Those who lack seats on corporate boards, who have non-business or non-economics backgrounds, who are male, and who are recruited externally adopt the plans at lower rates than their respective counterparts. The results portray presidents as exercising circumscribed agency, strategizing on the basis of their personal and professional experiences and making a difference even under inhospitable circumstances.